Non-stationary effects of growth on the survival of North American Atlantic salmon (Salmo salar). (16th September 2021) - Tillotson, Michael D; Sheehan, Timothy F; Ellingson, Brandon; Haas-Castro, Ruth E; Olmos, Maxime; Mills, Katherine E
Abstract: The productivity of Atlantic salmon ( Salmo salar ) has declined markedly since the 1980s,  in part because of changing ocean conditions, but mechanisms driving this decline remain unclear. Previous research has suggested differential recruitment dynamics between the continental stock groups, with post-smolt growth influencing the survival of populations in Europe, but not North America. We used a large, representative archive of North American, multi sea-winter salmon scales to reconstruct long-term changes in growth between 1968 and 2018. We then modeled relationships between annual growth indices, estimates of maturation rates, and post-smolt survival, while allowing for the possibility of non-stationary dynamics. We found that marine growth of MSW salmon has changed over the past 50 years, generally increasing despite declining survival. However, we found strong evidence of a non-stationary influence of post-smolt growth on survival. Prior to a period of rapid change in the ocean environment during the late 1980s,  post-smolt growth was positively related with survival, similar to the pattern observed in European populations. These findings suggest that the mechanisms determining marine survival of North American and European salmon populations may have diverged around 1990. More generally, our results highlight the importance of considering non-stationary dynamics when evaluating linkages between the environment, growth, and survival of Atlantic salmon.